Investigation of the Possibility to Solve Equations of Steady-State Mocks of Electric Power System - V. S. Safaryan (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents one of the methods which is to be applied for investigation of the possibility to solve equations of steady-state modes (ESM) of electric power system (EPS).The proposed method for investigation of ESM is developed on the basis of well-known Brauer’s theorem on a fixed point. In order to analyse ESM an inverted form of equations of nodal voltages has been used. These equations have been solved by iteration.The areas of EPS mode existence have been obtained for 3-nodal circuit which is supplied by direct and alternating current. The analysis of EPS modes has made it possible to obtain the required conditions in order to prove the existence of ESM solutions.